Status Dystonicus, Oculogyric Crisis and Paroxysmal Dyskinesia in a 25 Year-Old Woman with a Novel KCNMA1 Variant, K457E. (27th October 2020) - Buckley, Cliona; Williams, Jennifer; Munteanu, Tudor; King, Mary; Park, Su Mi; Meredith, Andrea L.; Lynch, Timothy
The diagnosis of a paroxysmal dyskinesia is difficult and status dystonicus is a rare life threatening movement disorder characterised by severe, frequent or continuous episodes of dystonic spasms. A 25 year old woman with chronic ataxia and paroxysmal dyskinesia presented with facial twitching, writhing of arms, oculogyric crisis and visual and auditory hallucinations. She developed respiratory failure and was ventilated. No cause was found so whole exome sequencing was performed and this revealed a novel, non-synonymous heterozygous variant in exon 11 of the KCNMA1 gene, K457E (c 1369A>G) in the patient but not her parents. This variant has not been previously reported in gnomAD or ClinVar. The finding of a de novo variant in a potassium channel gene guided a trial of the potassium channel antagonist 3, 4 diaminopyridine resulting in significant improvement, discharge from the intensive care unit and ultimately home.